A Window of Opportunity Remains Open : The Managing Director's Global Policy Agenda Update. (Policy Papers; Policy Paper ;, 2018)
The momentum behind the cyclical global expansion remains strong. But escalating trade conflicts and financial market volatility highlight downside risks beyond the next several quarters. To sustain the upswing, policy makers need to enhance financial sector resilience, start rebuilding policy space, and implement structural reforms-including on corruption and governance. Countries should work to promote an open and rulesbasedmultilateral trade system that works for all, and to durably reduce excess global imbalances. A cooperative approach to regulation will reap the benefits of financial technology, while addressing risks to stability and integrity. The Fund is embarking on major policy reviews, including on surveillance, the Financial Sector Assessment Program, program conditionality, concessional lending tools, debt sustainability analysis, and capacity development. We have also launched a comprehensive work program on the opportunities and challenges from digitalization.